(untitled) (Journal of Scientific Research, 2025)
Clerodendrum infortunatum is a well-known medicinal shrub with dark green leaves and whitish-pink flowers. Its extracts are used for the treatment of several diseases in traditional systems of medicine. It has phytomedicinal potential and is of great importance as it offers many promising health benefits. The objective of the study is to investigate the ethanolic extracts of leaves and flowers of Clerodendrum infortunatum for their antioxidant activity. The methods used include Ferric reducing power assay, DPPH, Hydrogen peroxide scavenging assay, and phosphomolybdate method. Total phenolic and flavonoid content are measured spectrophotometrically. The antifungal activity was evaluated using the food poison method, a technique that involves incorporating the test substance into a growth medium to observe its inhibitory effects on fungal growth. The screening of extracted phytochemicals is done by qualitative methods. The study shows the presence of various phytochemicals such as flavonoids, terpenoids, glycosides and phenolic components in the ethanolic extracts of leaf and flower of Clerodendrum infortunatum. The study also demonstrates that the ethanolic flower extract of Clerodendrum infortunatum exhibits the highest antioxidant activity. In contrast, the ethanolic leaf extract shows greater antifungal activity against Aspergillus niger and Aspergillus flavus compared to the flower extract.